2012
DOI: 10.1109/tap.2012.2189703
|View full text |Cite
|
Sign up to set email alerts
|

A Well-Conditioned Non-Iterative Approach to Solution of the Inverse Problem

Abstract: A novel methodology leading to well-conditioned formulation of the inverse scattering problem is proposed. The solution of the inverse scattering problem is made possible through elimination of the inherent ill-posedness of the inverse source problem. The latter is achieved by staging of the imaging experiment in a medium with the Green's function exhibiting focusing properties. The method is shown to cast the inverse source problem into a well-conditioned matrix equation without addition of the non-physical r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 30 publications
0
8
0
Order By: Relevance
“…The full-rank matrix F S indicates well-posedness of the underlying inverse scattering problem formulation. In [20], it was shown that such well-posed formulation of the inverse problem allows for its direct solution in analogous manner to the solution of the forward scattering problem. For comparison, in Fig.…”
Section: G S and F S Operatorsmentioning
confidence: 99%
See 1 more Smart Citation
“…The full-rank matrix F S indicates well-posedness of the underlying inverse scattering problem formulation. In [20], it was shown that such well-posed formulation of the inverse problem allows for its direct solution in analogous manner to the solution of the forward scattering problem. For comparison, in Fig.…”
Section: G S and F S Operatorsmentioning
confidence: 99%
“…the boundedness of the solution in Tikhonov regularization [19]). In [20], [21], it was shown, however, that the rank-deficiency of the discretized inverse scattering operator and thus the ill-posedness of the inverse scattering problem can be eliminated in rigorous compliance with Maxwell's Equations. For that purpose, the kernel of the forward scattering operator must be the Green's function of a focusing media and the sensor positions must be properly situated with respect to the locations of the sources in the imaging domain.…”
Section: Introductionmentioning
confidence: 99%
“…Okhmatovski et al () used an original method to noniteratively solve a nonlinear inverse scattered problem. They examined the advantage of using a Veselago lens in the imaging experiment to observe the super‐resolution using far‐field measured data only.…”
Section: Introductionmentioning
confidence: 99%
“…They used the following explanation for this effect: "even though … only scattered waves corresponding to propagating waves can be measured, the scattered waves contain high resolution information about the scatterer because of the evanescent-propagating waves conversion in a multiply scattered field." Okhmatovski et al (2012) used an original method to noniteratively solve a nonlinear inverse scattered problem. They examined the advantage of using a Veselago lens in the imaging experiment to observe the super-resolution using far-field measured data only.…”
Section: Introductionmentioning
confidence: 99%
“…Within the framework of these two approaches, some of the utilized techniques are (i ) increasing the number of antennas (or, probes) [1], (ii ) using multiple-frequency data sets [2], (iii ) using different boundary conditions [3], (iv ) using an appropriate Green's function [4], (v ) simultaneous use of transverse magnetic and electric data sets [5], (vi ) using appropriate data calibration techniques [6], (vii ) using more effective inversion algorithms and regularization techniques [7,8], (viii ) accurate MWT system modeling [9], (ix ) using a priori information [10], etc.…”
Section: Introductionmentioning
confidence: 99%